Exploring practitioners’ frames of reference for discomfort management of nursing home residents with dementia: A Q-methodology study. - Jiseon Bae; Yujeong Hong; Sung Ok Chang (Journal of Korean Gerontological Nursing, 2025)
Purpose: This study employed Q-methodology to explore frames of reference of nursing home practitioners in managing discomfort of residents with dementia. Methods: In-depth interviews were conducted with eight nursing home practitioners, all of whom had experience caring for residents with dementia. Additionally, a literature review on discomfort, its assessment, and interventions was conducted. Thirty-four practitioners as a P-sample, including nurses, care workers, social workers, and physical therapists, classified 34 Q-samples through Q-sorting. Data analysis was performed using the PQ-method 2.35 program. Results were interpreted based on factor arrays, post-interview data, and distribution of the P-sample. Results: Four Q-factors were identified as practitioners’ frames of references for discomfort management of nursing home residents: exploring possible management based on a synthesis of related clues, an individual assessment-based approach using possible assumptions, linking subtle changes to management direction based on a trusting relationship, and configuration-centered management direction using objective data. Conclusion: Utilizing nursing home practitioners’ frames of reference for managing demented residents’ discomfort can be used for developing strategies that can be used in practitioners’ education and promoting practice that can reduce discomfort of nursing home residents.